Slangs in Gen Alpha–Z: A Natural Language Processing Analysis and Its Impact in Educational Context - Fadlilah, Afi; Diani, Irma; Kusumah, Encep; Sugiharyanti, Eni; Miswaty, Titik Ceriyani (Universitas Pendidikan Mandalika, 2025)
Slang, especially among Generations Alpha and Z, functions as a dynamic tool for expressing identity, group belonging, creativity, and resistance to norms, shaped by digital platforms and used to signal cultural affiliation, shared values, and emotional stance in everyday communication. This study aims at evaluating the forms of slang language used by Generations Alpha and Z, linguistic patterns indirectly represent or construct social identity the influence of those slangs in educational context. This study followed a rigorous process to ensure data relevance, validity, and ethics by collecting publicly available Instagram texts from Generations Alpha and Z using purposive sampling. Data from public accounts were anonymized, scraped manually and automatically, then preprocessed through cleaning, tokenization, and normalization. NLP techniques and qualitative content analysis were applied to identify slang patterns and interpret their social meanings, revealing how slang reflects identity and cultural practices in digital youth communication. The analysis concludes that slang usage among Generations Alpha and Z on digital platforms like Instagram serves not merely as casual expression but as a communicative strategy that reflects social identity, group affiliation, and cultural values. Through a combination of computational and qualitative analysis, the study reveals that slang functions to assert community membership, convey emotional attitudes, and construct self-image in digital spaces. The emerging linguistic patterns highlight the significant role of informal language in digital literacy practices and educational interactions, underscoring the need for greater attention to youth language in both academic and cultural contexts. Previous studies have examined youth slang, but few have explored its role across digital platforms in shaping identity, especially using both computational and sociolinguistic approaches. The influence of slang in educational contexts also remains underexplored. This study addresses these gaps by analyzing slang's forms, functions, and meanings in digital youth communication.